Small States and Geopolitical Challenges: The Example of Qatar (2020-2025) - Aliyah Rafika; Mulawarman Hannase; M. Hamdan Basyar (Eduvest - Journal of Universal Studies, 2026)
Qatar is a notable example of a small state in the Arabian Peninsula, covering an area of 11,571 km², that has demonstrated geopolitical influence far exceeding its geographical boundaries. This study examines Qatar's complex geopolitical strategy in the face of pressure from dominant regional powers in the Middle East, with particular focus on the period 2020–2025. Employing a qualitative methodology and a case study approach, the study adopts an analytical framework that integrates small state foreign policy theory, hedging strategies, and soft power theory. The study analyzes how Qatar leverages its asymmetric strengths across three key domains energy resources, diplomacy, and media influence to project an outsized role in regional and global affairs. The study yields three principal findings. First, Qatar has consistently applied an asymmetric multi-alignment approach, enabling it to maintain concurrent relationships with multiple actors whose interests are in conflict. Second, the country has maximized niche diplomacy through conflict mediation, sports diplomacy initiatives, and strategic energy assets to build bargaining power disproportionate to its physical size. Third, hosting the 2022 FIFA World Cup and its active involvement in mediating the 2023–2024 Gaza conflict represents the culmination of Qatar's consolidation as an indispensable actor within the regional security architecture. In conclusion, Qatar demonstrates that small states can transcend structural limitations through asymmetric multi-alignment, niche diplomacy, and strategic soft power, effectively transforming inherent vulnerabilities into significant geopolitical influence thereby enriching the theoretical discourse on small state agency from a Middle Eastern perspective.